Chile Financial Sector Assessment Program : Detailed Assessment Report of CCLV (SSS), Contraparte Central, S.A. - World Bank Group (World Bank, Washington, DC, 2016)
The Central Bank of Chile (Banco Central de Chile, BCCh) and Chile’s Ministry of Finance, in their letter of January 9th, 2015, requested the World Bank to undertake a stand-alone Review of Standards and Codes (ROSC) module of the Principles for Financial Market Infrastructures (PFMI) of the Committee on Payments and Market Infrastructures (CPMI) and the International Organization of Securities Commission (IOSCO). The main tool used by the assessment was the CPSS-IOSCO Assessment Methodology for the Principles for Financial Market Infrastructure and the Responsibilities of Authorities”. Each of the FMIs and Chilean authorities, the Banco Central de Chile (BCCh), the Superintendencia de Valores y Seguros (SVS) and the Superintendencia de Bancos e Instituciones Financieras (SBIF) – completed a self-assessment for the PFMI and the Responsibilities of Authorities, respectively. On this basis, the WBG team and the local team conducted detailed interviews with senior and mid-level managers of all the respective institutions, and prepared the assessment reports. In addition to the self-assessments, other sources of information included the applicable laws and regulations, as well as each FMI’s main policies and internal documents (e.g. detailed policies, and processes and procedures for certain key areas) which were shared by the FMIs with the assessors, and other information available at each FMI’s website (e.g. statistics). The WBG and local teams also met with a number of users of these FMIs, including two large commercial banks and two brokers-dealers that are not part of local bank-lead conglomerates.